2013
DOI: 10.1155/2013/163292
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality and Female Literacy Rates in Developing Countries during 1970–2000: A Latent Growth Curve Analysis

Abstract: Background. The gross longitudinal relationship between female literacy and maternal mortality ratios has not been adequately investigated even though the knowledge of the relationship is crucial for designing maternal mortality reduction programs through female literacy campaigns and improvements. The objective of the study was to examine the dynamic relationship between female literacy and mortality ratios. A longitudinal study design spanning three decades, 1970-2000, was used. Country level data on 143 nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 58 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…For example, high scores in the political empowerment sub-index could be due to electoral quotas for women in societies with a history of strong discrimination against women (Pande & Ford, 2012), resulting in contradictory findings regarding women's political empowerment and maternal mortality. Needed are more prospective and/or longitudinal studies, such as DerSarkissian et al (2013) and Pillai, Maleku, and Wei (2013), which reported improvement in maternal health following an increase in the female literacy rate (DerSarkissian et al, 2013;Pillai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, high scores in the political empowerment sub-index could be due to electoral quotas for women in societies with a history of strong discrimination against women (Pande & Ford, 2012), resulting in contradictory findings regarding women's political empowerment and maternal mortality. Needed are more prospective and/or longitudinal studies, such as DerSarkissian et al (2013) and Pillai, Maleku, and Wei (2013), which reported improvement in maternal health following an increase in the female literacy rate (DerSarkissian et al, 2013;Pillai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the possibility exists that disparities identified in this study could change over time. As another future direction in research, studies can build on previous studies on adult mothers' pregnancy outcomes [62, 63] that examined population time trends in how social and economic factors are associated with preterm birth outcomes among teen mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Out of all maternal deaths, 99 percent occur in developing countries. Further, maternal mortality is higher among women living in rural areas, among poorer communities [3,4], and among those with low literacy [5].…”
Section: Introductionmentioning
confidence: 99%